Teaching Qualitative Research: - Andrew P. Carlin; Younhee H. Kim (Grounded Theory Review: An International Journal, 2019)
This paper concerns the teaching and iteration of Grounded Theory, taking published accounts referring to Grounded Theory as instructional materials on the workings of Grounded Theory. The paper identifies problems associated with later versions of Grounded Theory that are anticipated and avoided in The Discovery of Grounded Theory (Glaser & Strauss, 1967). It alerts practitioners and students to theoretical options in doing research. Based on a critical incident analysis of literatures as ’fieldwork sites’, looking at information science and dentistry research, this paper discusses iterations of qualitative research – particularly, what we call the versioning of Grounded Theory – in clinical settings and interdisciplinary studies. Reading accounts of qualitative studies revealed misapprehensions regarding the use of qualitative methods. Critical reading facilitates the examination of analytic claims, to alert researchers in interdisciplinary fields to adverse consequences of using inferior accounts.